Thermal Evolution of the Lithosphere in a Rift Environment as Inferred from the Geochemistry of Mantle Cumulates, Northern Victoria Land, Antarctica - C. Perinelli; ARMIENTI, PIETRO; L. Dallai (Journal of Petrology, 2011)
Among the abundant mantle xenoliths carried by the Cenozoic alkaline basalts of northern Victoria Land, Antarctica, we have studied a suite of clinopyroxene-rich cumulates collected at Browning Pass (Mt. Melbourne Volcanic Province), ranging in composition from wehrlites to clinopyroxenites. Clinopyroxenes belonging to both the Cr-diopside (wehrlites) and Al-augite series (ol-clinopyroxenites and clinopyroxenites) all show convex-upward REE patterns. Modal and cryptic metasomatism has variably affected the xenoliths, accounting for amphibole replacement of clinopyroxene and/or selective enrichment in incompatible elements. Chemical features, along with O–Sr–Nd isotopic data, indicate that both the parental magmas and the metasomatizing melts are related to the Cenozoic magmatic activity and imply the role of at least two mantle components with distinct isotopic fingerprints. The positive covariation between δ18Oolivine and the amount of modal olivine, and between δ18Oolivine and olivine Fo content, suggest that during the fractionation of olivine and pyroxene, the parent magma experienced a change in O-isotope composition; a low-δ18O melt component was not only added to the minerals during the metasomatic event but was also involved in the genesis of the parental melts. The Browning Pass cumulates are used to constrain the origin of the Antarctic Cenozoic magmatism from a heterogeneous mantle source whose depleted end-member is inferred to be the local lithospheric mantle, whereas the enriched end-member is represented by early metasomatic veins or domains emplaced into the depleted mantle during an amagmatic phase of rifting at the beginning of Ross Sea opening. Thermobarometric analysis of the process shows that the respective contribution to magma generation of the two end-members is related to the change of local thermal regime induced by an ‘edge effect’ in the mantle circulation at the lithospheric step between the thick East Antarctic craton and the thinned Ross Sea crust.